2022
DOI: 10.3390/ijms23169403
|View full text |Cite
|
Sign up to set email alerts
|

4-Phenylbutyric Acid (4-PBA) Derivatives Prevent SOD1 Amyloid Aggregation In Vitro with No Effect on Disease Progression in SOD1-ALS Mice

Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease characterized by the degeneration of motor neurons. Mutations in the superoxide dismutase (SOD1) gene, causing protein misfolding and aggregation, were suggested as the pathogenic mechanisms involved in familial ALS cases. In the present study, we investigated the potential therapeutic effect of C4 and C5, two derivatives of the chemical chaperone 4-phenylbutyric acid (4-PBA). By combining in vivo and in vitro techniques, we show that, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Pharmacokinetic (PK) studies demonstrated 98 and 99 can reach the brain and spinal cord only at high concentrations for a short period of time. 124,125 Mutant C9orf72 protein is encoded by the human C9orf72 gene, located on the short (p) arm of chromosome 9…”
Section: Reverse the Sod1 Proteins Aggregation Using Chemical Chaperonesmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacokinetic (PK) studies demonstrated 98 and 99 can reach the brain and spinal cord only at high concentrations for a short period of time. 124,125 Mutant C9orf72 protein is encoded by the human C9orf72 gene, located on the short (p) arm of chromosome 9…”
Section: Reverse the Sod1 Proteins Aggregation Using Chemical Chaperonesmentioning
confidence: 99%
“…While in vivo results showed that daily injections of 98 and 99 to SOD1 G93A mice following onset failed to extend the survival of SOD1 G93A mice or to improve their motor symptoms and did not reduce accumulation of misfolded SOD1 or improved the neuroinflammatory response in the spinal cord. Pharmacokinetic (PK) studies demonstrated 98 and 99 can reach the brain and spinal cord only at high concentrations for a short period of time 124,125 …”
Section: Mutations In the Sod1 Genementioning
confidence: 99%
“…Among proposed therapeutic targets, chemical chaperones, such as 4-phenylbutyric acid (4-PBA), which have the potential to restore protein homeostasis and improve cellular function, showed promising results. Alfahel et al investigated the potential therapeutic effect of two 4-PBA derivatives, N-(2-(1-methylpyrrolidin-2-yl)ethyl)-4-phenylbutanamide (compound 4, C4) and 2-isopropyl-4-phenylbutanoic acid (compound 5, C5) in the mutant SOD 1G93A mouse model of ALS [ 7 ]. They found that C4 or C5 daily injections in SOD1 G93A mice following onset failed to extend the survival of SOD 1G93A mice or to improve their motor symptoms.…”
mentioning
confidence: 99%